Aromatization of Heavy Naphtha using Modified Zeolite Supported Catalyst - Fakruldin, A; Ramli, A; I. Abdul Mutalib, M (International Journal of Engineering and Technology, 2019)
Growing population has increased the dependency toward sustainable energy sources. Research industries have groomed their facilities to find alternative sources of energy. Heavy naphtha can be converted to value added fuel such as gasoline via catalytic conversion. Modified zeolite supported catalyst was employed for aromatization of heavy naphtha to gasoline like liquid. The catalyst was impregnated with 3 wt.% Fe via wet impregnation method. The catalysts prepared were send for characterization using BET, FESEM-EDX and TPD. Catalytic activity was performed at 430-480 Â°C, LHSV 1 hr-1 and 14 bar in a fixed-bed continuous reactor. The result revealed that the by adding Fe onto the zeolite supported catalyst provides slight improvement of yield.Â